2022
DOI: 10.3390/su14031699
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ Satisfaction vis-à-vis Environmental and Socio-Morphological Aspects for Sustainability and Decent Work

Abstract: This study examines worker satisfaction vis-à-vis outdoor places in terms of their environmental and socio-morphological aspects. Numerous studies have considered decent work as the eighth goal of sustainable development. However, it is worth investigating outdoor workers’ satisfaction with a view to the practical design of the surrounding context that supports their work in outdoor places. Using bibliometric analysis, this study investigates possible approaches toward providing decent work in a public place i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…The results supported the levels of these spaces that should be planned to meet the residents’ satisfaction and sense of attachment [ 58 ]. As such, satisfaction with open shared spaces relates to satisfaction with the overall quality of life [ 6 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results supported the levels of these spaces that should be planned to meet the residents’ satisfaction and sense of attachment [ 58 ]. As such, satisfaction with open shared spaces relates to satisfaction with the overall quality of life [ 6 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is an assumption that a city with well-defined public spaces can be considered a district with a strong identity, regardless of its weaknesses in other aspects (Oktay et al ., 2015). Knez (2005) and Elshater et al . (2022a) showed that climate, topographic and landscape conditions are a part of the “residents” place identification (Elshater et al.…”
Section: Literature Reviewmentioning
confidence: 92%
“…There is an assumption that a city with well-defined public spaces can be considered a district with a strong identity, regardless of its weaknesses in other aspects (Oktay et al, 2015). Knez (2005) and Elshater et al (2022a) showed that climate, topographic and landscape conditions are a part of the "residents" place identification (Elshater et al, 2022a). As for the landscape, a locally characteristic and identifiable landscape (both natural and artificial) could also be highly effective on urban identity (Kaymaz, 2013;Oktay et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature discussed some of the contextual challenges that cities in the Global South face, such as access to finance, lack of basic facilities and infrastructure, sanitation issues, exposure to air, food and water pollution, general lack of technical skill in construction labour and awareness of sustainability concepts (Elshater et al ., 2022). However , literature indicates insufficient fundamental information, such as reliable urban population censuses, which hinders the use of global sustainability indicators (Kamble and Bahadure, 2020).…”
Section: Introductionmentioning
confidence: 99%